A política de assistência social no enfrentamento ao fenômeno violência da Rede Governamental no Município de Cascavel - Dal Molin, Susana Medeiros (2012)
This paper aims to discuss the Social Assistance Policy in confronting the phenomenon of violence Government Network in Cascavel. To achieve this we trace the following instruments: Empirical Note, Bibliographic and Documental Research, with which base our research. To this end, we seek to understand the development of Social Policy in Brazil, from its origin to the establishment of the Unified Social Services (ITS) as well as build the diagnosis of the violence committed against children and adolescents through the Network Socioassistencial Government in Cascavel / PR, in 2011. This paper does not intend to conduct a thorough analysis of the entire path taken by Social Services, to be effective as Public Policy, is what we want to list some elements to understand the referral of the state in social contradictions existing in our society in refers to assistance actions in confronting the phenomenon violence against children and adolescents, with the particularity the municipality of Cascavel / PR.